Changes in plasma bile acids are associated with gallbladder stones and polyps - Linshi Wu; Yinping Wang; Sibo Zhu; Xunxia Bao; Zhiliang Fu; Timing Zhen; Zhiqing Yuan; Qiwei Li; Zheng Deng; Jianhua Sun; Tao Chen (BMC Gastroenterology, 2020)
Abstract Background The development of gallbladder disease (GBD) is related to bile acid (BA) metabolism, and the rate of BA circulation increases the risk of biliary cancer. However, it is unclear whether patterns of circulating bile acids (BAs) change in patients with benign GBDs such as gallbladder stones and polyps. Herein, we compared and characterised plasma BA profiles in patients with cholecystolithiasis and non-neoplastic polyps with healthy controls, and explored relationships between plasma BA profiles, demographics, and laboratory test indices. Methods A total of 330 subjects (13 healthy controls, 292 cholecystolithiasis and 25 non-neoplastic polyps) were recruited and plasma BA profiles including 14 metabolites from patients with pathologically confirmed cholecystolithiasis and non-neoplastic polyps were compared with controls. BAs were quantitated by liquid chromatography and mass spectrometry, and statistical and regression analyses of demographics and laboratory test indices were performed. Results Females displayed a higher burden of GBD than males (63.36% cholecystolithiasis, 60% non-neoplastic polyps). Cholecystolithiasis and non-neoplastic polyps were associated with increased plasma total secondary BAs, while levels of primary BAs were lower than in healthy controls. Plasma ursodeoxycholic acid (UDCA), tauroursodeoxycholic acid (TUDCA), glycyurdeoxycholic acid (GUDCA), taurochenodeoxycholic acid (TCDCA) and glycochenodeoxycholic acid (GCDCA) were decreased significantly in GBDs, and ursodeoxycholic acid (UDCA) was negatively correlated with white blood cell count and neutrophil percentage. Conclusions Secondary BA levels were higher in patients with cholecystolithiasis and non-neoplastic polyps. White blood cell count and percentage of neutrophil in peripheral blood were negatively correlated with UDCA, indicating an anti-inflammation effect of UDCA.